LncRNA DUXAP8 as a prognostic biomarker for various cancers: A meta-analysis and bioinformatics analysis - Wang, Yongfeng; Jiang, Xianglai; Zhang, Dongzhi; Zhao, Yuanbin; Han, Xiaoyong; Zhu, Lihui; Ren, Jingyao; Liu, Yubin; You, Jiarong; Wang, Haolan; Cai, Hui (Frontiers in Genetics, 2022)
Background Dual homeoboxes A pseudogene 8 (DUXAP8) is a newly discovered long noncoding RNA that has been shown to function as an oncogene in a variety of human malignant cancers. By integrating available data, this meta-analysis sought to determine the relationship between clinical prognosis and DUXAP8 expression levels in diverse malignancies. Materials and methods A systematic search was performed to identify eligible studies from several electronic databases from their inception to October 25, 2021. Pooled odds ratios and hazard ratios with 95% CI were used to estimate the association between DUXAP8 expression and survival. For survival analysis, the Kaplan-Meier method and COX analysis were used. Furthermore, we utilized Spearman's correlation analysis to explore the correlation between DUXAP8 and tumor mutational burden (TMB), microsatellite instability (MSI), the related genes of mismatch repair (MMR), DNA methyltransferases (DNMTs), and immune checkpoint biomarkers. Results Our findings indicated that overexpression of DUXAP8 was related to poor overall survival (OS) (HR = 1.63, 95% CI, 1.49-1.77, P <0. 001). In addition, elevated DUXAP8 expression was closely related to poor OS in several cancers in the TCGA database. Moreover, DUXAP8 expression has been associated with TMB, MSI, and MMR in a variety of malignancies. Conclusion This study revealed that DUXAP8 might serve as a prognostic biomarker and potential therapeutic target for cancer. It can be used to improve cancer diagnosis, discover potential treatment targets, and improve prognosis.